Pengaruh Promosi, Komunikasi dan Budaya Organisasi terhadap Kinerja Karyawan pada PT Central Mandiri Cemerlang - Cut Fitri Rostina; Ryanda Perdana Gozali; Yosita Chuanda; Kevin Triady; Rudy Kurniawan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
The purpose of this study was to examine the effect of promotion, communication and organizational culture on the performance of employees of PT. Central Mandiri Cemerlang. The approach taken in this research is an associative approach. Saturated sampling technique is a sampling technique when all members of the population are used as samples. The sample in this study amounted to 88 people. Data analysis was carried out by multiple linear regression analysis through classical assumption test consisting of normality test, multicollinearity test and heteroscedasticity test and hypothesis testing consisting of simultaneous test, partial test, and coefficient of determination. The results showed that partially and simultaneously promotion, communication and organizational culture had a significant effect on the performance of the employees of PT. Central Mandiri Cemerlang.